Pengaruh Pemahaman Akad Dan Religiusitas Terhadap Minat Melakukan Transaksi Di Bank Syariah - Ismail, Abdul Hadi; Pradesyah, Riyan (AGHNIYA : Jurnal Ekonomi Islam, 2024)
This study aims to see the influence of contract understanding, and religiosity on the interest of FAI UMSU students in making transactions in Islamic banks. As is known, the current development of Islamic financial institutions, especially Islamic banks, is inseparable from the understanding of Islamic finance itself. So many researchers have conducted research on understanding, related to people's interest in making transactions at Islamic banks. This research uses a quantitative approach, by distributing questionnaires to FAI UMSU students. Data processing is carried out using the SPSS application. As for the results, partially the variable Understanding of the Contract (X1) had a significant effect on the Interest in Transaction of FAI UMSU Students at Bank Syariah (Y), then the variable of Religiosity (X2) had a significant effect on the Interest in Transaction of FAI UMSU Students at Bank Syariah (Y). Meanwhile, simultaneously, the variable of Understanding of Contract (X1) and the variable of Religiosity (X2) had an effect on the Interest of FAI UMSU Students in Transaction Interest in Sharia Bank (Y), by 88.3%, while the remaining 11.7% was influenced by other variables that were not in the study.